2019
DOI: 10.1051/0004-6361/201834564
|View full text |Cite
|
Sign up to set email alerts
|

The VLT-FLAMES Tarantula Survey

Abstract: Aims. We estimate physical parameters for the late-type massive stars observed as part of the VLT-FLAMES Tarantula Survey (VFTS) in the 30 Doradus region of the Large Magellanic Cloud (LMC). Methods. The observational sample comprises 20 candidate red supergiants (RSGs) which are the reddest ((B − V) > 1 mag) and brightest (V < 16 mag) objects in the VFTS. We use optical and near-infrared (near-IR) photometry to estimate their temperatures and luminosities, and introduce the luminosity–age diagram to est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 73 publications
6
44
0
Order By: Relevance
“…As shown in Fig. 5, our result is compatible with the recent observational estimates by Beasor et al (2019) and Britavskiy et al (2019). Our analytic result also agrees with corresponding estimates for clusters up to 1000 Myr (see Figure 2 of Niederhofer et al 2015).…”
Section: Comparison To Observed Star Clusterssupporting
confidence: 92%
“…As shown in Fig. 5, our result is compatible with the recent observational estimates by Beasor et al (2019) and Britavskiy et al (2019). Our analytic result also agrees with corresponding estimates for clusters up to 1000 Myr (see Figure 2 of Niederhofer et al 2015).…”
Section: Comparison To Observed Star Clusterssupporting
confidence: 92%
“…We note that the suggestion of Milone et al (2018), that the main-sequence population of NGC 330 consists of 32 Myr and 40 Myr populations, cannot explain the spread in luminosities that is observed in the RSG population. Using the luminosity distribution, we estimate a red straggler fraction of 50%, in excellent agreement with Britavskiy et al (2019).…”
Section: Resultssupporting
confidence: 72%
“…Table 2 compiles the physical properties of NGC 330 and summarises the main results of this study. Britavskiy et al (2019) suggested to use an arbitrary cutoff of log(L/L ) = 4.3 to distinguish between RSGs and lower-A&A proofs: manuscript no. 36741corr Notes.…”
Section: Rsg Age Of Ngc 330mentioning
confidence: 99%
See 2 more Smart Citations